(untitled) (International Journal of Studies in Nursing, 2019)
Background: Identified on an acute care behavioral health unit has been a gap in nursing education and knowledge about opioid addiction and pain management. Nurses are often frustrated that there seems to be no clear way to manage acute pain in individuals suffering with opioid addiction. Because of difficult behavior sometimes displayed in those with opioid addiction, nurses may be prone to attitudes that reflect bias on their part when administering care. The psychiatric nurses need to learn about the disease model of addiction so its premise can be shared with the opioid addicted patients and their families. Purpose: The purpose of this proposal is to create a plan to teach the Behavioral Health nurses about opioid addiction and management of acute pain to help those afflicted with opioid addiction. Plan: The plan for addressing the gap includes education about opioid addiction, the barriers presented by stigma and bias, and the use of opioid replacement therapy to manage acute pain in those with opioid addiction. Patient education will focus on addiction as a disease and the impact of stigma on those with the disease. Implementation: Implementation of the project will include the development of two classes about management of acute pain in opioid addicted patients emphasizing education of the nurse and patient as the prime solution to this dilemma. The classes will stress the need to model conversations with psychiatric physicians to develop strategies to manage acute pain in patients with opioid addiction. Conclusion: Opioid replacement therapy seems to be the only answer for individuals in need of rehabilitation to end their burden of addiction. It should be accessible to any person with addiction to opioids in every healthcare setting.